PENGARUH PELATIHAN KERJA, MOTIVASI KERJA DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. STAR AUTO MULTILINK MEDAN - Cing Cing; Khomeiny Yunior; Cindy Selvia (Jurnal Ilmiah METHONOMI, 2021)
This research aim is to test and analyze the effect of job training, job motivation and job supervision on employee performance at PT. Star Auto Multilink Medan. Employee performance degradation caused by lack of job training, motivation and supervision of work. The research method uses quantitative. The population is amounted to 196 employees and the sample amounted to 62 employees of the sampling. Hypothesis testing in a partial job training, job motivation and job supervision has positive and significant effect on employee performance at PT. Star Auto Multilink Medan and simultaneously job training, job motivation and job supervision has positive and significant effect on employee performance at PT. Star Auto Multilink Medan.